Manufacturing and performance evaluation of medical radiation shielding fiber with plasma thermal spray coating technology - Seon-Chil Kim (Nature Portfolio, 2021)
Abstract Lead, which has been used for radiation shielding in medicine, is currently sought to be replaced by an eco-friendly shielding material. Therefore, it should be replaced with shielding materials possessing excellent processability and radiation shielding performance similar to that of lead. In this study, a new process technology was developed focusing on the processability of tungsten, a representative eco-friendly shielding material. It is difficult to reproduce the shielding performance when using the method of coating nonwoven fabrics with a liquid using tungsten powder on a polymer material, which is adopted to ensure the flexibility of the shielding fabric. To address this, tungsten powder was sprayed on the fabric using a plasma thermal spray coating process and coated to a thickness of 0.2 mm to evaluate the shielding performance. Compared to standard lead with a thickness of 0.2 mm, the shielding efficiency differed by approximately 15%. Since the developed process can maintain the amount of injection in an area, it is possible to ensure the reproducibility of the shielding performance and automated process for mass production. This approach is economically feasible as it does not entail the mixing of polymer materials; hence, it can be used for preparing radiation shielding clothing for medical institutions.